Evaluación del impacto financiero de la aplicación del beneficio de la devolución del impuesto a la renta - Marquez Narvaez, Ludy Mariuxi (2015)
The proposed integration project involves the application of an Integrated Operational Guidance is designed for any company regardless of their economic activity, their understanding and management will be designed for anyone who is knowledgeable in accounting taxation, also indicate what are the enabling roles and how they should be filled as required by law Proof of Sales in Ecuador. It will contain in detail all parameters or requirements that must be met for a company to claim a refund of income tax, which improved profitability. As the researchers García, Juan Pablo Mateo and Santiago says, the income tax is the second highest grossing income country, this is due to the tax incentives from the IRS to taxpayers. For information gathering technique or interview method is used, because the information obtained in the interview will be a high degree of reliability. The proposal is viable and accessible to all companies because they do not demand special programs that have a representative, but a core program of Microsoft Office economic value. It arises that the State, through the Internal Revenue Service to advertise through internet, newspapers, radio and television about the tax benefits provided by the state for taxpayers to request the return of taxes provided they comply with all Integral parameters present the Operational Guidelines, there is no retaliation by the state and does not need a lawyer to ask for it. Because in many cases the lack of information and misconception of reality taxpayers are not welcome tax benefits.